Flexibilität und Anpassungsfähigkeit von Beschäftigten mit dualer Berufsausbildung - Alexandra Fedorets; Alexandra Spitz-Oener (Zeitschrift für ArbeitsmarktForschung - Journal for Labour Market Research, 2011)
– We examine the occupational and wage mobility of employees with a vocational training degree obtained in the German dual system of apprenticeship training. The conceptual framework is based on the human capital theory and the search theory under the assumption of variation in occupational contents over time. The regression analysis shows that occupational changes are positively correlated with individual wages. It provides evidence that the degree of correlation depends on the similarity between the content of occupation in which the individual was trained and the kind of occupation in which the individual was employed at the time of the survey. Further, it shows that the voluntariness of occupational change also contributes to the degree of correlation. We measure the similarity of occupational contents with the task-based approach. In contrast to the results for West Germany, occupational changes in East Germany after reunification are associated with wage penalties. This negative wage effect is persistent and can be observed even 10 years after the occupational change. The general results suggest that human capital which was accumulated during apprenticeship training, is transferable across different occupations.
Keywords: 330; Ausbildungsabsolventen; berufliche Mobilität; Einkommenseffekte; erlernter Beruf; ausgeübter Beruf; Berufswechsel; regionaler Vergleich; Humankapitalansatz; Arbeitsplatzsuchtheorie; BIBB/IAB-Erhebung; Berufsverlauf; Ostdeutschland; Westdeutschland; Bundesrepublik Deutschland